Mapping the scientific literature on obstetric and perinatal health among sexual and gender minoritized (SGM) childbearing people and their infants: a scoping review - Aimee K. Huang; Alison R. Schulte; Mary-Frances E. Hall; Laura Y. Chen; Sanjana Srinivasan; Carol Mita; Aava B. Jahan; Kodiak R. S. Soled; Brittany M. Charlton (BMC, 2024)
Abstract Background Evidence suggests sexual and gender minoritized (SGM) childbearing individuals and their infants experience more adverse obstetric and perinatal outcomes compared to their cisgender, heterosexual counterparts. This study aimed to comprehensively map obstetric and perinatal physical health literature among SGM populations and their infants and identify knowledge gaps. Methods PubMed, Embase, CINAHL, and Web of Science Core Collection were systematically searched to identify published studies reporting obstetric and perinatal outcomes in SGM individuals or their infants. Study characteristics, sample characteristics, and outcome findings were systematically extracted and analyzed. Results Our search yielded 8,740 records; 55 studies (1981-2023) were included. Sexual orientation was measured by self-identification (72%), behavior (55%), and attraction (9%). Only one study captured all three dimensions. Inconsistent measures of sexual orientation and gender identity (SOGI) were common, and 68% conflated sex and gender. Most (85%) focused on sexual minorities, while 31% addressed gender minorities. Demographic measures employed varied widely and were inconsistent; 35% lacked race/ethnicity data, and 44% lacked socioeconomic data. Most studies (78%) examined outcomes among SGM individuals, primarily focusing on morbidity and pregnancy outcomes. Pregnancy termination was most frequently studied, while pregnancy and childbirth complications (e.g., gestational hypertension, postpartum hemorrhage) were rarely examined. Evidence of disparities were mixed. Infant outcomes were investigated in 60% of the studies, focusing on preterm birth and low birthweight. Disparities were noted among different sexual orientation and racial/ethnic groups. Qualitative insights highlighted how stigma and discriminatory care settings can lead to adverse pregnancy and birth outcomes. Conclusions Frequent conflation of sex and gender and a lack of standardized SOGI measures hinder the comparison and synthesis of existing evidence. Nuanced sociodemographic data should be collected to understand the implications of intersecting identities. Findings on perinatal health disparities were mixed, highlighting the need for standardized SOGI measures and comprehensive sociodemographic data. The impact of stigma and discriminatory care on adverse outcomes underscores the need for inclusive healthcare environments. Future research should address these gaps; research on SGM perinatal outcomes remains urgently lacking. Trial registration The review protocol was developed a priori in February 2023, registered on Open Science Framework ( https://doi.org/10.17605/OSF.IO/5DQV4 ) and published in BMJ Open ( https://bmjopen.bmj.com/content/13/11/e075443 ).